R-seecka model for research supervision and the effect on academic and career growth of international graduate students in Malaysia - Amzat, Ismail Hussein; Walters, Lynne Masel; Walters, Tim; Yusuf, Byabazaire; Teslikhan, Muhajir (University of Malaya, 2020)
Malaysia is committed to growing its research universities and its reputation as one of the world's largest educational service providers. Malaysia has sizable population of international students, and the country is recalibrating its strategy and planning to increase the number of international students to 200,000 by 2020. However, neither the Malaysian government nor the universities have created the synergy to increase the wellbeing of international students, their research progress and, most critically, academic supervision. Therefore, this study aims to investigate the direct effect of research supervision, that is, the supervisor’s encouragement, content knowledge, and availability, and campus environment and facilities on international students’ academic and career growth. This study proposes a model, called R-SEECKA (relationships, supervision, environment; encouragement; content knowledge and availability) for effective research supervision and practice in Malaysian public universities. The sample size consists of 450 international graduate students from different countries studying at six Malaysian public universities. It uses quantitative methods and SmartPLS for data analysis. Findings of this study reported the effect of encouragement, environment, relationship, availability and content knowledge on international graduate students’ academic and career growth. It is also reported that encouragement and motivation from the supervisor was the strongest predictor of academic and career growth, followed by campus environment/facilities. The paper offers recommendations and suggestions for future research to see how much research supervision has improved and international students have progressed in research in Malaysia. The authors note that the R-SEECKA model may be applied at universities in other countries and to other student populations to assess the impact of research supervision on their academic and career growth.